Deborah and Barak at Huqoq (Biblical archaeology review, 2022)
The article reports that archaeologists from the University of North Carolina at Chapel Hill have discovered Huqoq mosaic, the earliest known depiction of Deborah, the Judge, at Huqoq in northern Israel.